Devices for pre-sterilszation treatment of endoscopes by ozone and ultrasound - Taran, V.S.; Krasnyj, V.V.; Schebetun, A.V.; Lozina, A.S. (Вопросы атомной науки и техники, 2014)
In the article, the specially designed devices for pre-sterilization treatment of laparoscopic, endoscopic and other long-length surgical equipment from organic compounds (blood and alkali) in ultrasonic tank-container with ozone has been proposed. The first device was equipped with a bath (up to 30 l), ten ultrasonic emitters with a total power 300 W, and four modular ozone generators based on dielectric barrier discharges. The second device equipped with 3.5 liter volume bath was also designed having a glass pipe 1 meter long, 8 cm in diameter with one ozone module and immersion ultrasonic emitter. During treatment, the ozonized water was injected both into the internal and external surfaces of endoscopes. The output ozone concentration reached 30 mg/l with dry air flow rate 0.3 l/min. Phenolphthalein test and "Delatest" solution method determined the remains of alkali and blood, respectively. Представлены специально разработанные устройства для предстерилизационной обработки лапароскопического, эндоскопического и другого длинномерного хирургического оборудования от органических соединений (крови) и щелочи в ультразвуковой ванне с озоном. Первое устройство было оснащено ванной (до 30 л), десятью ультразвуковыми излучателями с общей мощностью 300 Вт, и четырьмя модульными генераторами озона на основе диэлектрического барьерного разряда. Второе устройство – это рабочая камера, объемом 3,5 л в форме стеклянной трубы длиной 1 м и диаметром 8 см с одним модулем озона и погружным ультразвуковым излучателем. Во время обработки озонированная вода вводилась во внутренние и наружные поверхности эндоскопов. Выходная концентрация озона – 30 мг/л при скорости протока воздуха – 0,3 л/мин. Используя метод фенолфталеиновой пробы и тест-систему "Delatest" определяли остатки щелочи и крови соответственно Представлені спеціально розроблені пристрої для передстерилізаційної обробки лапароскопічного, ендоскопічного та іншого довгомірного хірургічного обладнання від органічних сполук (крові) і лугу в ультразвуковій ванні з озоном. Перший пристрій був оснащений ванною (до 30 л), десятьма ультразвуковими випромінювачами з загальною потужністю 300 Вт і чотирма модульними генераторами озону на основі діелектричного бар'єрного розряду. Другий пристрій - це робоча камера, об'ємом 3,5 л у формі скляної труби довжиною 1 м і діаметром 8 см з одним модулем озону і занурювальним ультразвуковим випромінювачем. Під час обробки озонована вода вводилася у внутрішні і зовнішні поверхні ендоскопів. Вихідна концентрація озону – 30 мг/л при швидкості протоку повітря – 0,3 л/хв. Використовуючи метод фенолфталеїнової проби і тест-систему "Delatest" визначали залишки лугу і крові відповідно.